Sumbangsih pemikiran Johannes Gijsbertus de Casparis terhadap perkembangan studi kesejarahan di Indonesia (1948-1990) - Almasyhur, Muhammad Bima Raihan; Adyatma, Aliif Rif’at Dhahulat; Septian, Nur Rahman Dias (Universitas Negeri Malang, 2024)
Abstract Johannes Gijsbertus de Casparis, a Dutch historian and archaeologist, focused on the study of classical Indonesian history. His important contributions through various writings greatly influenced the study of Indonesian paleography and epigraphy. This article uses a literature study with a historical approach to analyze de Casparis' influence in the study of Indonesian history in the period 1948-1990. The research shows that de Casparis' thoughts had a great influence on the development of historical studies, especially in the fields of epigraphy and paleography. One of his works, “Indonesian Inscriptions,” became a major reference in such studies, providing a systematic framework for interpreting inscriptions. In addition, de Casparis was instrumental in mentoring prominent archaeologists such as M. Boechari, who helped advance the National Archaeological Research Center and made it highly regarded by international academics, thus advancing the field of Indonesian archaeology significantly. Abstrak Johannes Gijsbertus de Casparis, seorang sejarawan dan arkeolog asal Belanda, yang memiliki fokus pada studi sejarah klasik Indonesia. Kontribusinya yang penting melalui berbagai tulisan sangat mempengaruhi studi paleografi dan epigrafi Indonesia. Artikel ini menggunakan studi literatur dengan pendekatan historis untuk menganalisis pengaruh de Casparis dalam studi sejarah Indonesia pada periode 1948-1990. Penelitian menunjukkan bahwa pemikiran de Casparis berpengaruh besar dalam perkembangan studi sejarah, khususnya di bidang epigrafi dan paleografi. Salah satu karyanya,